The Assyrian Eastern Frontier Girdi Gulak, a Fortified Settlement in the Zagros Foothills. Preliminary Results of the Danish Archaeological Expedition to Iraq - Colantoni, Carlo; Makinson, Martin; Skuldbøl, Tim (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2018)
The eastern frontier of the Neo-Assyrian Empire is an important area of research for understanding the state, its organisation and its defence. Our knowledge of these borderlands was until recently limited, though it is generally accepted that the foothills of the Zagros Mountains marked a frontier region (e.g. Liverani 2004; Radner et al. 2016). New archaeological research in the Zagros foothills of Iraq has shed light on the eastern frontiers of the Assyrian empire (see e.g. Radner et al. 2016; Miglus 2016; Ur et al. 2013).